Updating the distribution of the genus Callitriche (Plantaginaceae) in Italy from the study of the Herbarium Centrale Italicum collections - Lastrucci, Lorenzo; Saiani, Daniele; Mugnai, Alessio; Ferretti, Giulio; Viciani, Daniele (Mediterranean Botany, 2024)
The first results of a herbariological study on the genus Callitriche L. at the Central Italian Herbarium (Herbarium Centrale Italicum) of the Museum of Natural History of the University of Florence are presented. This genus represents a critical group from a systematic and taxonomic point of view, as the diagnostic characters mainly consist in details of the reproductive structures that are difficult to observe and interpret. The herbarium specimens represent a material suitable for study only if they have anthers and especially ripe fruits. The study of these samples has brought to light the presence of material from newly reported locations for various Italian regions. In some cases, the reports derive from original new revisions, in other cases they are the result of the discovery and confirmation of previous revisions not incorporated by the modern Italian floras.